Korelasi Penilaian Proses Belajar Model Guided Inquiry Learning dan Guided Discovery Learning Dengan Hasil Belajar Formatif Pada Materi Kesetimbangan Kimia - Farid Gusranda; Zonalia Fitriza (Universitas Negeri Padang, 2020)
This study aims to determine the relationship between the assessment of students’ learning processes that use the Guided Inquiry Learning and Guided Discovery Learning learning models for formative outcomes. This research uses a quantitative approach with correlation analysis between two research variables. Data on the assessment of student learning processes is obtained from the evaluation given during the learning process, which is at the conclusion stage of each meeting. Student formative learning outcomes data were obtained from diagnostic test questions in the form of reasoned multiple-choice questions and descriptions at the end of chemical equilibrium learning. The results showed the relationship between the assessment of learning processes with student learning outcomes classified as High with a correlation coefficient of 0.81 for class XI Science 1 with Guided Discovery learning model and 0.86 for class XI Science 4 with Guided Inquiry learning learning model.